Evaluation of clinical spectrum of Hepatitis A in children admitted at a tertiary care center in Western Nepal - Subedi, Nabaraj; Shrestha, Bandana; Bhattarai, Arjun; Paudel, Shankar; KC, Namrata (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: Hepatitis A is one of the causes of morbidity and mortality in children in developing countries like Nepal. Hepatitis A virus is a positive-strand RNA virus that is transmitted feco-orally through person-to-person contact. Lack of awareness, overcrowding, and poor sanitation have led to increased infection mainly in many rural areas. This study was conducted to assess the clinical course of hepatitis A, blood parameters and its associated complications in patients admitted pediatric ward. Methods: A hospital-based cross-sectional study was conducted on pediatric patients who had presented with icterus. Only serologically confirmed cases by the detection of IgM antibodies against Hepatitis A virus (HAV), ELISA were included in the study group. The clinical course and lab profiles of the patients were analyzed. Results: A total of 75 patients were positive for HAV IgM A (serology) and were included in the study. The majority of children seen were in the age group of 5 to 12 years (51%). The most common symptoms were icterus. More than a fivefold rise in AST and ALT (SGPT) was seen in 58 cases (77.3%) and 62 cases (82.6%) respectively. More than 2,000 U/L of AST and ALT were seen in 10 cases (13.3%) and 14 cases (18.6%) respectively. Conclusions: It was found that vomiting, abdominal pain and icterus were most common clinical features. Elevated prothrombin time and raised liver enzymes were most common lab findings. The most common abdominal ultrasound finding was ascites. No patients presented with severe complications.